Radioactive contamination and climate warming affect physiological performance of Chornobyl barn swallows. - Zbyszek Boratyński; Timothy A Mousseau; Anders Pape Møller (PLoS ONE)
Global warming and degradation of natural habitats are the two main factors causing ecophysiological stress on individuals and risk for biodiversity. Hyperthermia is a common response to stress in homeothermic animals, in particular to heat, pathogens and environmental contamination. Resilience of biological systems to global warming may be deteriorated in polluted habitats. Here we investigated how body temperature of a wild bird, the barn swallow (Hirundo rustica), responded to global warming while simultaneously exposed to radioactive contamination from the Chernobyl accident. Our results showed that both high air temperatures (t = 15.55, df = 335, p < 0.0001) and elevated environmental radioactive contamination (t = 5.18, df = 8.09, p = 0.0008) increased internal body temperature of individuals. The additive effect suggests that birds might suffer hyperthermia in locally contaminated habitat (1.47% body temperature increase) while simultaneously exposed to globally rising temperatures (1.95% body temperature increase), potentially reducing the fitness of individual and the maintenance of breeding colonies. The cumulative and interactive negative effects of multiple stressors, such as those emerging from increasing habitat degradation and climate change, will likely contribute to biodiversity losses globally.